A importância das competências em informação para o profissional de secretariado: um estudo aplicado no Centro de Ciências Médicas da Universidade Federal da Paraíba – Campus I - Cruz, Luciana Cabral da (2018)
Over the years, information has become recognized as a key element in all segments of society. Its importance is so great that staying informed has become critical to keeping up to date and in tune with the world. The development of Information Technologies not only contributed to the emergence of this new concept of society but also brought with it the increase of the flow of information in its different sources. The current scenario presents complexities and requires new skills of access and use of information, among these skills are information skills. From this reality, the present study aimed to analyze the aspects of the information competences that contribute to the effective performance of its functions. The study was applied with the secretaries of the Center of Medical Sciences of Campus I of the Federal University of Paraíba. The present study also identified the sources of access to information used by secretarial professionals of the Center of Medical Sciences of the Federal University of Paraíba; noted how secretarial professionals make use of the information they have acquired in their working relationships; mapped the categories of sources and uses of information by secretariat professionals and suggested a skills development program that could contribute to improving access to and use of information. In methodological terms, it was a field research, exploratory and descriptive, delimited by the qualitative and quantitative approaches. As a data collection instrument, a structured interview script was used. With the result of the research it was found that the secretaries receive several information and not all are useful for their professional demands, the information received are not enough to perform their tasks and they always resort to other sources of information search. It is hoped that this research may spark discussions about information competencies and contribute to new research being undertaken, since these competencies are a relatively new and expanding field in Brazil. It is also hoped to stimulate the reflection and to provoke discussions on the subject, competences in information, within the scope of the Federal University of Paraíba.